Epidemiological, clinical, and therapeutic profiles of patients treated for arterial hypertension in the Cardiology Department of Kinshasa General Hospital (Formerly Maman Yemo), DRC - Motuta, Christian Amisi; Koko, Lisette Loboto; Biembe, Elvis; Lutete, Michel Kelani; Mawunu, Monizi; Masengo, Colette Ashande; Koto-Te-Nyiwa Ngbolua, Jean-Paul (Orapuh Journal, 2024)
IntroductionArtery hypertension (AH) is still the main risk factor for several complications, including coronary heart disease, stroke, peripheral artery disease, and renal dysfunction.PurposeThis study aimed to determine the epidemiological and therapeutic characteristics of patients treated for high blood pressure at the Cardiology Department of the General Hospital of Kinshasa. Methodology: A retrospective descriptive study of records of patients admitted for hypertension to the Department of Cardiology of the General Hospital of Kinshasa was conducted. This study covers two years from January 1, 2022, to January 31, 2023.ResultsThe incidence was 9.2% in the cardiology department and 2.9% in the general hospital. The average age was 55.4 to 12.3, the extremes were 25 to 90, and patients were 51 to 75 years old (54.1%). Women are more affected (59.5%), and the male-female ratio is 0.6. Alcohol consumption is the main complaint in 35.1 percent of cases, while the most reported clinical signs are dizziness, headaches, and muscle dyspnea in 89.3 percent, 77.1 percent, and 53.4 percent, respectively. As for treatment, 100% of patients received medical care and 55.7 % of patients had low-salt diets. According to the distribution of prescribed drugs, diuretics (100%), conversion enzyme inhibitors (78.6%), anticalcitamines (66.4%), and beta-blockers (41.2%) are the most prescribed drugs. In 94.6% of cases, the result was good, with a death rate of 5.4%.ConclusionWe can say that arterial hypertension is now a major concern for all medical and paramedical staff. Despite the efforts currently being made, we still see many patients with hypertension every day.